Analysis of the Need for Development of Physics Electronic Modules using the Kaili Ethnic Culture Approach - Ahmad Ilham Kurniawan; Sukarmin Sukarmin; Daru Wahyuningsih (Universitas Papua, Jurusan Pendidikan Fisika FKIP Unipa, 2026)
The main challenge in physics education is the assumption by students that the material is difficult and abstract, and this is exacerbated by the threat of globalization to the preservation of local wisdom. The purpose of this study is to describe the needs analysis for the development of an electronic module on temperature and heat based on ethnoscience (Batik bomba) of the Kaili tribe culture for 11th grade MIPA students. The research used the 4D Research and Development (R&D) model. This research was in the define stage and used descriptive data analysis techniques. The research was conducted as a survey, with data collected through a needs analysis questionnaire for physics teachers and 38 grade XI high school students in Central Sulawesi. The results show that 100% of teachers need more interesting and contextual teaching materials, while 50% experience difficulties in developing independent modules. From the students' perspective, 88% want to learn the application of physics in real life, and 85% are motivated by examples of applications in local culture. The identified needs include: (1) the development of ethnoscience modules that integrate the local culture of Kaili (Bomba Batik Weaving), (2) the strengthening of practical learning, and (3) the availability of digital learning resources (e-modules). Based on these findings, the development of Kaili Ethnic Science electronic modules is urgently needed as a solution to overcome teaching obstacles while fostering positive attitudes and appreciation for local culture.